Expository Learning pada Musik Tradisional I Sulim Batak Toba - Emmi Simangunsong; Junita Batubara; Kamaluddin Galingging (Universitas Negeri Medan, 2018)
This article discusses about expository learning on the learning strategy of music instrument sulim taught on the class of Traditional Music I Toba Batak. For the study of Expository learning on sulim music the research wasdone in five steps which are preparation, presentation, correlation, generalization, and application. These five steps done to increase and raise students’s motivation and interest to learn the sulim instrument. This topic conducted through descriptive qualitative research. The results obtained in this study was that learning strategy of expository learning is a corresponding strategy applied to the process of learning the music instrument sulim Toba Batak. The student fascinatingly interested and motivated to learn playing the sulim instrument. Expository learning strategy on the class of Traditional Music I Toba Batak have a positive impact from the success of the students to gain a maximum assessment.